Dietary and supplemental folate and the risk of left- and right-sided colorectal cancer - Clapin, H.; Fritschi, Lin; Iacopetta, B.; Heyworth, J. (Lawrence Erlbaum Associates, Inc, 2012)
Epidemiological evidence suggests that folate may lower the risk of colorectal cancer (CRC) although studies have been inconsistent and some have indicated differences in the effects of naturally occurring dietary folate and the synthetic form of this vitamin, folic acid. Most studies to date have considered CRC as a single disease; however, cancers that develop on the left and right sides of the colorectum display important phenotypic differences, suggesting they may also have different risk factors. A population-based case-control study was conducted in Western Australia to examine the relationship between intake of both natural dietary folate and supplements containing folic acid and the risk of left- and right-sided CRC. Data were available for 850 cases (575 left-sided and 275 right-sided) and 958 controls. Odds ratios were calculated using multinomial logistic regression models. There was no association between natural dietary folate intake and risk of either left-or right-sided CRC. Supplement use similarly had no significant effect on right-sided CRC. However, long-term supplement users (4+ yr) were at lower risk of left-sided CRC than those who had not taken supplements (OR = 0.65, 95% CI, 0.50–0.86) and there was a significant trend in risk reduction as duration of use increased (P < 0.01).